Role of paraoxonase-1 as a diagnostic marker for feline infectious peritonitis. (June 2021) - Meazzi, S.; Paltrinieri, S.; Lauzi, S.; Stranieri, A.; Brentali, I.; Ferriani, R.; Rossi, G.; Giordano, A.
Highlights: Paraoxonase-1 (PON-1) activity was evaluated as a biomarker in cats. Lowest PON-1 activities were observed with feline infectious peritonitis (FIP). Low paraoxonase-1 activities were also observed with septic effusions. PON-1 activity accurately discriminated FIP from similar clinical conditions. The utility of PON-1 activity to diagnose non-effusive FIP needs further study. Abstract: Feline infectious peritonitis (FIP) is characterised by the presence of systemic inflammation accompanied by oxidative stress. Paraoxonase-1 (PON-1) is a negative acute phase reactant produced by the liver. A paraoxon-based method has been validated to measure PON-1 activity in feline serum. The aim of this study was to investigate the usefulness of PON-1 activity as a biomarker to discriminate FIP from other diseases with similar clinical signs. Of 159 cats enrolled, 71 were healthy, 34 had FIP and 54 had another disease but presented with clinical signs that could be consistent with FIP. PON-1 activity was lower ( P <0.0001) in cats with FIP (median, 26.55 U/L; range, 5.40–78.20 U/L) compared to healthy (median, 87.5 U/L; range, 46.60–215.50 U/L) and Non-FIP Sick group cats (median, 57.90 U/L; range, 3.80–122.60 U/L). Two receiver operating characteristic curves were used to determine the thresholds that maximised the performance of PON-1 activity in predicting FIP both from a screening and diagnostic point of view. A threshold of 78.30 U/L yielded a sensitivity of 100%, a specificity of 50.4%, and a negative likelihood ratio of 0.00 (screening curve). While a threshold of 24.90 U/L maximised specificity (94.4%), had a sensitivity of 44.1%, and increased the likelihood ratio to 7.94, making PON-1 activity a good confirmatory test for FIP (diagnostic curve). Using these thresholds, serum PON-1 activity showed good diagnostic performance in discriminating FIP affected cats from cats with other inflammatory conditions.